A Case of Evan's Syndrome Induced by Vedolizumab. Issue 1 (January 2019) - Jen, Henry; Morganstern, Bradley; D'Souza, Lionel
Abstract : Abstract: Vedolizumab is a monoclonal antibody against the ɑ4β7 integrin receptor used for the treatment of ulcerative colitis and Crohn's disease. Clinical trials have shown vedolizumab to be a safe and highly effective therapy in treating inflammatory bowel disease. Its unique gut-specific mechanism of action has made it an attractive agent in recent years. However, vedolizumab's side effect profile and long-term effects are not fully understood. We report a patient with ulcerative colitis who presented with epistaxis 1 week after receiving the first induction dose of vedolizumab found to have a severe immune-mediated thrombocytopenia and hemolytic anemia, otherwise known as Evan's syndrome.